Analisis Perkembangan kemampuan Membaca Permulaan Pada Siswa Sekolah Dasar Menggunakan Metode Montessori - Wanda Alifia Nur Aminullah; Vevy Liansari (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
This study aims to determine the development of basic reading skills in students who have reading difficulties using the Montessori method of public elementary school with students case studies. This study used a quantitative experimental method with a Pre-Experimental Design and One Group Pretest-Posttest Design. This research was conducted in accordance with the stages of learning to read using the Montessori method. The research instrument used was the basic reading assessment. The data collection technique uses the results of the pre-test and post-test scores. The data that has been obtained was analyzed using SPSS with paired sample t-test and independent sample t-test. The result of test paired sample t-test Sig. (2-tailed) of 0.000 <0.05 so that the difference in pre-test and post-test scores is significant. Independent t-test Sig. (2-tailed) 0.011 <0.05 so that there is a significant difference between the differences in the pre-test and post-test results of conducive students and non-conducive students. So it can be concluded that the Montessori method is effective in increasing the development of students basic reading skills, but the difference in the effectiveness of the Montessori method can be different based on student conductivity.